2009
DOI: 10.1515/hc.2009.15.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Preparation And Characterization Of Phospholanes And Phospha Sugars As Novel Anti-Cancer Agents

Abstract: Diastereo isomericerythro and threo forms of 2,3-epoxy-l-phenylphospholane 1-oxides were synthesized from threo and erythro forms of 2-bromo-3-hydroxy-l-phenylphospholane 1-oxides being prepared from l-phenyl-2-phospholene 1-oxide. Alternatively, the epoxides were also prepared by the epoxidation of the 2-phospholene with peroxides such as sodium peroxide and hydrogen peroxide. The reactivity and regioselectivity for the reaction of erythro and threo forms of the 2,3-epoxides with nucleophiles were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…103 Phosphorus-based glycomimetics contain a phosphorus atom in place of the anomeric carbon or in place of the endocyclic oxygen. 104,105 Three main classes of such compounds can be distinguished: phospha-, phosphono-(phostones), and phosphino-sugars (phostines, 1,2-oxaphosphinanes). The phosphinolactone group (O-PQO) in phostones and phostines serves as a bioisostere of hemiacetals (O-C-OH) with phosphorus replacing the anomeric carbon.…”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%
“…103 Phosphorus-based glycomimetics contain a phosphorus atom in place of the anomeric carbon or in place of the endocyclic oxygen. 104,105 Three main classes of such compounds can be distinguished: phospha-, phosphono-(phostones), and phosphino-sugars (phostines, 1,2-oxaphosphinanes). The phosphinolactone group (O-PQO) in phostones and phostines serves as a bioisostere of hemiacetals (O-C-OH) with phosphorus replacing the anomeric carbon.…”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%
“…In the same article, he also observed a moderate antiproliferative effect of phosphinine 1-oxides 4 and 5 [3]. Ito reported [4] that phospholane derivatives 6 and 7 exhibited significant antitumor activities against leukemia cells such as the K562 and U937 cell lines, as well as solid cancer cells such as stomach cancer and lung cancer. Further mechanistic studies by Western blotting showed that such compounds could enhance the expression of IER5 and then suppressed the expression of Cdc25B, which are responsible for their antitumor activity [5].…”
Section: Introductionmentioning
confidence: 86%
“…Phosphorus‐based sugars and phosphorous containing glycomimetics are cyclic molecules that present a phosphorus atom in place of the anomeric carbon or alternatively in place or linked to the endocyclic oxygen. Depending on how the phosphorus atom is inserted into the cycle, three main classes of compounds can be obtained: phospha‐sugars, phosphono‐sugars (or phostones), and phosphino‐sugars (phostines or 1,2‐oxaphosphinanes), schematically reported below (Figure ) . Some phosphorus heterocycles that are being referred to as phospha‐sugars do not contain hydroxyl substituents on the cyclic skeleton and thus are not really carbohydrate analogues in a strict sense.…”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%